The Crime of Trafficking in Persons in Indonesia: Applying Islamic Criminal Law to Develop a Victim Rehabilitation Framework - amilang amilang; Amir Ilyas; Hamzah Halim; Saharuddin Saharuddin; Bazarova Dildora Baxadirovna (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2025)
Rehabilitation for victims of human trafficking must include physical, psychological, and social recovery, as well as the reintegration of victims into their families and communities. This research aims to analyze the rehabilitation of victims of human trafficking as a form of the application of Islamic criminal law. This research uses a qualitative approach with a juridical-empirical method. The research results emphasize that the urgency of rehabilitation for victims of human trafficking is very important considering the complex and multidimensional nature of the impact of this crime, which includes physical, psychological, and social aspects. Victims often experience prolonged trauma, health issues, and loss of rights and dignity due to exploitation. Comprehensive rehabilitation services not only help victims to function socially in a proper manner and restore their rights, but also prevent retraumatization during the recovery and law enforcement processes. The reform of Islamic criminal law in regulating the rehabilitation of victims of human trafficking crimes has become very important to address contemporary social and legal challenges. Based on the principles of maqashid sharia such as the preservation of life, intellect, and social welfare, this reform offers a humanistic and contextual approach, making Islamic criminal law not only a tool of punishment but also an instrument of rehabilitation and restorative justice